Evaluation of the addiction prevention program "Entre todos" - Celia Menéndez-Hernández; Leticia- Concepción V; Juan- Carlos (MLS Journals S.L., 2018)
Introduction. This article evaluates an addiction and drug addiction prevention program. The evaluated program is "Entre Todos" (Proyecto Hombre Association, 2000) which was developed in 2017 with a sample of 135 5th and 6th grade students from every school located in Torrox (Málaga, Spain). Method. The design of this evaluative research was mixed, combined with a qualitative methodology -through interviews and observation and a quantitative methodology, through surveys. In addition to the students' sample, 5 teachers took part in the evaluation, who collaborated with the program's development. The research's objective was to evaluate the quality of the program and to determine possible improvement areas for the future. The quantitative data was analyzed in a descriptive way (frequencies and percentages). The qualitative data was subject to a content analysis. Results. The results allowed to evaluate the program's design, execution and resources, aiming at identifying the strategies that allow to better meet the detected needs and better adapt to the program's addressees. Discussion. Apart from evaluating the program, detecting some weaknesses as well as areas for improvement, it is concluded that implementing and evaluating projects like this one is key. The fact of working with families and the attention to the integral personal development are essential in preventions programs aimed at adolescents.